Collecting plant genetic diversity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Collecting plant genetic diversity: technical guidelines edited by L Guarino, V Ramanatha Rao and R Reid 1995 ISBN 0 85193 964 0